Characteristics of decomposition and nutrient release of green manure returning to kiwifruit orchards in southern Shaanxi province - WANG Lü; WU Yuhong; CHEN Hao; QIN Yuhang; HAO Jing; HAO Xingshun; LIU Qi; LI Danni; ZHANG Chengbing (Guoshu xuebao)
[Objective] Green manure is a clean biological organic fertilizer source. Reasonable planting and utilization of green manures between rows in kiwifruit orchards is an important technical measure to solve the problems of shortage of organic fertilizer sources, protect the soil environment, improve soil quality, and promote sustainable agricultural development. The soil fertilization effect of green manure is influenced by the type of green manure, soil habitat, and orchard climate. Therefore, the decomposition characteristics and nutrient release patterns of different varieties of green manures returned to the field in kiwifruit orchards were studied, in order to provide theoretical basis for the planting and utilization of green manure in kiwifruit orchards in southern Shaanxi and the fertilization in the later stage of growth. [Methods] The field net bag burial method was used to study the decomposition characteristics and nutrient release patterns of four types of green manure, Lolium perenne L., Vicia sati-va L., Vicia villosa Roth., and Astragalus sinicus L., in the 10 cm soil layer between kiwifruit rows after 142 days of compaction. [Results] The decomposition was divided into three stages: rapid decomposition period (0-24 days), moderate decomposition period (25-41 days), and slow decomposition period (42-142 days). After 142 days of decomposition, the cumulative decomposition rates of Lolium perenne L., V. sativa L., V. villosa Roth., and Astragalus sinicus L. were 93.63%, 93.37%, 91.48%, and 74.45%, respectively. The average cumulative release rates of C, N, P2O5, and K2O nutrients were 88.23%, 82.95%, 98.58%, and 77.15%, respectively. The average N release amounts were 2 373.58, 144.76, 156.30, and 16.10 kg·hm-2, respectively. The decomposition rates of C, N, and K2O fluctuated significantly 24 days before decomposition, while the decomposition rates of phosphorus fluctuated significantly 41 days before decomposition. After 142 days of decomposition, the C, N, K2O, and P2O5 release rates of Lolium perenne L. were 3 015.28, 132.38, 274.53, and 23.72 kg·hm-2, respectively, with nutrient cumulative release rates of 93.63%, 89.16%, 99.28%, and 92.65%, respectively. The nutrient cumulative release rates of V. sativa L. were 2 278.46, 193.69, 109.56, and 18.46 kg·hm-2, respectively, with nutrient cumulative release rates of 91.48%, 89.85%, 98.53%, and 82.47%, respectively. For V. villosa Roth, they were 2 855.68, 173.49, 156.61, and 17.09 kg·hm-2, respectively. The cumulative nutrient release rates of C, N, K2O, and P2O5 were 93.37%, 83.67%, 98.72%, and 73.88%, respectively. For Astragalus sinicus L. they were 1 344.89, 78.47, 84.50, and 5.12 kg·hm-2, respectively. The cumulative nutrient release rates of C, N, K2O, and P2O5 were 74.45%, 69.11%, 97.81%, and 59.60%, respectively. The nutrient release rates of the four types of green manure were K2O>C>N>P2O5, with the average cumulative release rates of 98.58%, 88.23%, 82.95%, and 77.15%, respectively. The decrease in dry matter mass among green manure varieties was in the order of Lolium perenne L.> V. sativa L.>V. villosa Roth.> Astragalus sinicus L.. The decomposition rate was in the order of Lolium perenne L.>V. villosa Roth.> V. sativa L.>Astragalus sinicus L. The release levels of C and K2O nutrients from various varieties of green manure were Lolium perenne L.> V. sativa L.>V. villosa Roth.> Astragalus sinicus L.. The release levels of N nutrients were in the order of V. villosa Roth.>Lolium perenne L.>V. sativa L.>Astragalus sinicus L.. The release levels of P2O5 nutrients were Lolium perenne L.>V. villosa Roth.>V. sativa L.>Astragalus sinicus L.. The release of C, K2O, and P2O5 from Lolium perenne L. was the highest, while the release of N from V. villosa Roth. was the highest. The cumulative decomposition rate and nutrient release rate of Astragalus sinicus L. were lower than those of the other three varieties. The C/N ratios of the four types of green manure in the order of Astragalus sinicus L.>Lolium perenne L.>V. sativa L.>V. villosa Roth., with ratios of 12.99, 12.74, 11.30, and 9.70, respectively. The C/N ratio of green manure was significantly positively correlated with dry mass, decomposition rate, release rates of C, N, P2O5, and K2O, as well as the accumulation of C, P2O5, and K2O. It was significantly negatively correlated with the accumulation and release rates of C and P2O5. [Conclusion] The application of three types of green manure, namely ryegrass, sweet potato, and arrow pea, can provide carbon, nitrogen, potassium, and phosphorus nutrients for kiwifruit orchards at 2 716.47, 166.52, 180.23, and 19.76 kg·hm-2, respectively. The application of green manure is during the periods of bud break, leaf development, flowering, and fruit setting. Adequate nutrient supply during these periods is the key to ensure fruit growth, development, and quality formation. The nutrients provided by the application of green manure play an important role in kiwifruit root growth and nutrient absorption. Returning green manure to the field enhances the effectiveness and persistence of soil nutrients, enabling sustained supply of nutrients for kiwifruit growth in the middle and later stages. Therefore, in kiwifruit orchards in southern Shaanxi, applying L. perenne L., V. villosa Roth., and V. sativa L. as green manure enables sustained release nutrients into the soil, providing necessary nutrients for the growth and development of fruit trees.